Agro-Ecological Sustainability of Farming Systems in Punjab and Haryana - Chhabilendra Roul (Journal of the Indian Society of Soil Science, 2022)
This paper focuses on the quantitative assessment of the ecological sustainability of agricultural production in Punjab and Haryana, the breadbasket of India. To compute the sustainability, we used indicators on (i) state of soil and its management (ii) weather, climate, and water management, and (iii) biodiversity, environment and climate change. Using data from secondary sources, a composite index of ecological sustainability and indices for three individual dimensions were computed. The indices show a moderate level of ecological sustainability in Haryana and Punjab. Biodiversity and environment were the most eroded dimensions of sustainability needing special attention. Though important for improving soil health, the traditional leguminous-crop-based cropping patterns are disappearing from these states. The residues of crops are rich repository of carbon and bacteria, and the nitrogen supplied by legume crops facilitates their decomposition and their conversion to soil-building organic matter. Both the states need to focus on policy changes regarding pricing water and power and incentivizing the adoption of microirrigation and other modern irrigation practices to improve agricultural sustainability in these aspects.